A formação integral na educação infantil aliada à Pedagogia Inaciana - Gallo, Caren Adriana Mendes (Universidade do Vale do Rio dos Sinos, 2021)
This job intend to discuss about the importance of a education in an integral mode since the childhood and which the importance of Ignatian Pedagogy in this process. Seeking for answer questions related about school:What is this environment? What kind of individual we must to form? Is in the childhood we had fundamental base for the moral development, social and cultural; and the school come to be a structure like a support point and reference for the individual’s life in the society, allowing it a human being transformation. With a globalized world, we know schools are in sert in a world much more capitalist with conservative ideals, that prepared people for the labor market, leaving the human and spiritual side without their due value.
Keywords: Pedagogia Inaciana; Infância; Integral; Pedagogy Inaciana; Childhood